Lithofacies and depositional models of lacustrine mixed siliciclastic–carbonate–evaporite rocks in the Eocene Qianjiang Formation, Qianjiang Depression, Jianghan Basin, China - Kang Wen; Shang Xu; Qilu Xu; Zhen Li; Qianzhu Xiong; Yongzhi Cheng; Huilin Xu; Bingchang Liu; Dong Yang; Shiqiang Wu; Libin Guo (Journal of Asian Earth Sciences, 2026)

Biodegradation and toxicity attenuation of bisphenol A by Sphingopyxis granuli XYQ201: mechanism elucidation and wastewater application - Xiaoyan Qi; Tao Li; Danni Gao; Huilin Jiang; Guohua Zhu; Xiawen Qiu; Qiaoqi Guo; Yixin Ouyang; Huajun Feng; Hai Xiang (Bioresource Technology, 2026)

RNA methylation in cardiovascular remodeling: Molecular mechanisms, biomarkers, and therapeutic strategies - Huilin Li; Qiming Fan; Jiajun Sang; Chengxia Kan; Xiaodong Sun; Kexin Zhang (Molecular Biology Reports, 2026)

Exploring the mechanism of Panax notoginseng injection in the treatment of skin wound based on network pharmacology and experimental verification - Yibin Li; Qinglin Li; Jun Liu; Juncen Li; Huaman Geng; Genke Li; Huilin Huang; Chen Jin; Jie Luo; Zhihong Zhang (Journal of Molecular Histology, 2026)

UV-assisted electrokinetic remediation of Cr(VI) in contaminated soil: Efficiency and interfacial processes in deionized water and citric acid media - Yibo Zhang; Mingdong Song; Qiu Yu; Zao Jiang; Xiaoning Li; Huilin Li; Yi Zheng (Journal of Environmental Chemical Engineering, 2026)

Wind and white: the dual controls of cold waves on surface urban heat islands in China - Xiang Li; Wenfeng Zhan; Huilin Du; Shasha Wang; Chunli Wang; Yingying Ji; Chenguang Wang; Zihan Liu; Jiufeng Li; Long Li; Yihan Gao; Shuang Ge (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

ZnIn2S4 nanoflower-decorated TiO2 nanobelts for boosting photocatalytic hydrogen evolution - Ligang Ma; Xinlan Li; Tingting Chen; Jingxuan Zhou; Jiulei Zhao; Yichi Zhang; Huilin Jiang; Xiaoqian Ai (Fuel, 2026)

Comprehensive insights into bitter compounds of food and medicine homologous substances: categorization, identification, and perception mechanisms - Cuixue Li; Yuxin Pei; Yuzhen Wang; Huilin Liu; Baoguo Sun (Food Chemistry, 2026)

Machine learning-assisted Mn-N-C nanozyme colorimetric sensor array for trace-level detection of biogenic amines in meat - Jiajie Li; Changlong Dai; Shuyu Li; Zhuqian Xiao; Wei Wang; Huilin Zheng; Hongpeng Wang; Jun Huang (Food Chemistry, 2026)

Decoding cadmium toxicity in spiders: F-actin and Hippo pathway insights - Zhongyuan Li; Siqi Huang; Hua Wang; Zhuoman Wang; Cuimei Gao; Zijian Jiang; Yanfen Zheng; Lingru Feng; Huilin Yang (Environmental Pollution, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

A TAPT-BTTA@MnO2-based fluorescence-colorimetric-photothermal multimodal sensing platform for reliable determination of organophosphorus pesticides - Suyu Li; Yuzhen Wang; Huilin Liu; Baoguo Sun (Analytica Chimica Acta, 2026)

Rhizosphere soil microbial community is associated with the resistance of purple-stemmed Panax notoginseng to root rot disease - Qinzu Li; Linyan Zhao; Wumei Xu; Fugang Wei; Shaozhou Yang; Liyan Tian; Huilin Guan (Rhizosphere, 2026)

Flower-like CoNi-LDH/PtNPs composites for highly efficient electrochemical sensing of methyl parathion in vegetables - Yibo Song; Jingjing Cui; Chunlei He; Jing Cao; Huilin Li; Wenjing Zhao; Mingfei Pan; Shuo Wang (Food Chemistry, 2026)

Comprehensive insights into time-dependent dynamic of maturation time on flavor formation in low-salt fermented tilapia - Huilin Zhao; Ke Zhang; Li Yang; Yan Guo; Wei Yang; Lei Qin; Xuhui Huang (Food Chemistry, 2026)

Bitterness in medicine and food homology substances: An overview of compound types, influence factors, and taste-masking methods - Yuzhen Wang; Yuxin Pei; Cuixue Li; Dianwei Zhang; Huilin Liu; Baoguo Sun (Food Chemistry, 2026)

Engineering exposed crystal planes of ZIF-8 to tune the surface coordination environment for stable zinc metal anodes - Yao Dai; Wenhao Li; Huilin Fan; Runguo Zheng; Zhiyuan Wang; Sha Liu; Hongyu Sun; Yanguo Liu (Chemical Engineering Journal, 2026)

Rewiring of Nestin+ Cells Through PTBP1/PKM2 Axis Restores Notch-Dependent Neural Circuit Regeneration After Spinal Cord Injury - Wei Hu; Meng Li; Yicheng Ding; Xinyi Cheng; Junchao Luo; Junjie Niu; Xiaozhong Zhou; Huilin Yang; Lulu Zhang; Qin Shi; Xingzhi Liu (Neuroscience Bulletin, 2026)

A Q-learning-driven multi-objective algorithm for dynamic hybrid flow shop rescheduling with setup and new job arrivals - Yaju Chen; Junqing Li; Huilin Wang; Yeqiu Yan; Li Wei; Haonan Song (Swarm and Evolutionary Computation, 2026)

ST-MMF-Net: AIS-driven spatiotemporal multi-modal fusion network for ship trajectory prediction - Jiangkun Wang; Huilin Pan; Yong’ao Qian; Jiankun Li; Xiaoya Hu (Ocean Engineering, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Fe/N Co-doped sludge-derived biochar enables rapid Maduramicin adsorption via coupled hydrophobic partitioning and Fe–N complexation - Xinying Li; Huilin Wan; Zhifu Tian; Min Ji; Siyuan Zhai; Qinghua Ouyang; Na Lin; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2026)

From planarization-assisted footing to halogen-induced gripping: cooperative additive engineering of molecular assembly for efficient organic solar cells - Xinrui Li; Chenghao Jiang; Xiaoyang Du; Huilin Wu; Jia Zhu; Hui Lin; Caijun Zheng; Silu Tao (Chemical Engineering Journal, 2026)

Genome-wide analyses of the Nodulin-like gene family in sorghum - Shuhan Feng; Yaru Yu; Qian Wu; Xuanru Shi; Mengyao Song; Haojie Zhang; Mingjie Qi; Haoqi Lv; Kangqi Du; Huilin Zhang; Ying Li; Xiaolin Song; et al. (Genetic Resources and Crop Evolution, 2026)

Soil quality evaluation and limiting factor analysis of a coal mine area with different reclamation years and microtopographies based on multi-method minimum data set - Ke Zhang; Huilin Li; Yunxiao Chen; Xu Chen; Ximin Cui; Yan Ma; Yi Shi (Environmental Monitoring and Assessment, 2026)

Sulfur-based mixotrophic denitrification with PCL/corncob for low C/N mariculture wastewater: Kinetics, microbial mechanism, machine learning optimization and continuous-flow validation - Liwei Wang; Haowei Wen; Xiefa Song; Weimin Yu; Teng Ma; Zuoliang Sun; Zheng Zhou; Huilin Wang; Dengpan Dong; Xueshu Han; Meng Li (Aquaculture, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Metal contamination in migratory waterbirds along the East Asian-Australasian flyway: Evidence from a critical wetland stopover site on the Yunnan-Guizhou Plateau - Mumo Li; Huilin Luo; Wenzhang Dai; Benshuang Sun; Hongyang Dai; Shuang Yang; Yubao Duan; Shilong Liu; Xu Luo (Environmental Pollution, 2026)

Heterogeneous responses of secondary organic aerosol sources to long-term emission reductions in megacity Shanghai, China - Huilin Hu; Yunyi Liang; Ting Li; Yongliang She; Yao Wang; Ziyue Li; Chenxi Li; Jianlin Hu; Jingyi Li; Yue Zhao (Environmental Pollution, 2026)

Computational simulation-assisted magnetic fluorescent molecularly imprinted polymer for the effective recognition and detection of multi-tetracycline antibiotics - Xuan Liu; Mengmeng Gao; Zimeng Liu; Xiaochun Hu; Huilin Li; Yaguang Yun; Gaoshuang Hu; Mingfei Pan; Shuo Wang (Chemical Engineering Journal, 2026)

Wetting-induced microstructural evolution and mechanical degradation of granitic residual soils in Southeastern China - Xiaoyu Yi; Wenkai Feng; Huilin Bai; Shuangquan Li; Jiachen Zhao; Yanlong Zhao (Bulletin of Engineering Geology and the Environment, 2026)

More caution or more lenient: deciphering the role of negative affect in recognition and inference - Lu Li; Hehe Lu; Ke Jiang; Huilin Qiu; Chunting Lin (Cognitive Processing, 2026)

Eco-friendly bricks manufactured from municipal sewage sludge before and after electrodialytic recovery of phosphorus - Huilin Li; Mireia Brisa Martin; Marta Gamón Ramón; Lisbeth M. Ottosen (Waste Management, 2026)

The role and molecular mechanism of Shikonin in promoting odontogenic differentiation of human dental pulp stem cells - Xiaoyue Zhang; Lingling Gong; Qing Zhao; Zixuan Huang; Manni Le; Huilin Zhang; Xiaocong Wang; Ming Li; Shusheng Zhang (Tissue and Cell, 2026)

Global urban intra-park surface cooling gradients and their key landscape thresholds - Yingying Ji; Wenfeng Zhan; Shasha Wang; Xiang Li; Chunli Wang; Huilin Du; Yihan Gao; Jiufeng Li; Chenguang Wang (Sustainable Cities and Society, 2026)

Multiple interactions tailoring nanocellulosic-carbon dots membrane for synergistic, self-cleaning and recyclable interception of heavy metals/dyes pollutants in wastewater - Mengxing Yan; Hanqi Dong; Huilin Chen; Xiao Xiao; Weixing Li; Qiang Yong; Zhe Ling (Journal of Hazardous Materials, 2026)

AIE-active UiO-66@PtNPs nanozyme-amplified fluorescence and colorimetric dual-signal magnetic immunosensing platform for effective detection of aflatoxin B1 in food products - Yixin Wang; Jing Cao; Mingxia Song; Huilin Li; Hao Wang; Mingfei Pan; Shuo Wang (Food Chemistry, 2026)

Data-driven optimization of coagulation process for high-organic sea cucumber aquaculture wastewater: Interpretable ML modeling and robust TSS soft sensor development - Liwei Wang; Haowei Wen; Xiang Feng; Xiefa Song; Zuoliang Sun; Huilin Wang; Dengpan Dong; Meng Li (Aquacultural Engineering, 2026)

Adaptive Exposure Control for Aerial Cameras in Maritime Scenes - Haiying Liu; Yingchao Li; Shilong Xu; Huaide Zhou; Huilin Jiang (Journal of Marine Science and Engineering, 2026)
Maritime aerial imaging is strongly affected by rapid illumination variations induced by dynamic sea conditions, which often cause conventional exposure control approaches to misinterpret intrinsic scene brightness as overexposure resulting from elevated camera settings. To overcome this issue, an adaptive exposure control framework based on a Glare-Aware Attention Network is proposed, implemented within an end-to-end dual-branch architecture. The framework utilizes an Exposure State Encoding (ESE) module to encode the current frame’s exposure parameters as conditional vectors, thereby resolving physical ambiguities in scene understanding. A Glare-Aware Spatial Attention (GASA) mechanism is further introduced, incorporating a glare prior map (GPM) generated using a “high-luminance, low-texture” heuristic to explicitly suppress sun glint effects. A Scene Difficulty-Adaptive Loss Weighting (SDAW) scheme is designed to adaptively regulate loss weights, and region-aware evaluation metrics, KREA and ISR, are defined. On a self-collected maritime aerial imaging dataset, the proposed approach significantly outperforms both traditional and deep learning-based methods in terms of full-frame and region-level performance metrics. Compared with the multi-task CNN baseline that has the closest parameter count, it achieves a 1.7 dB gain in PSNR. Cross-dataset validation on SeaDronesSee, temporal consistency analysis, and embedded platform testing further support the generalization and real-time feasibility of the proposed solution. Offering a high-accuracy, region-aware exposure control solution for aerial cameras in complex sea surface scenarios.

Oleuropein restores oocyte competence during SIRT1 inhibition via SIRT1/NRF2-mediated redox and metabolic reprogramming in porcine oocytes - Nenghao Cao; Huilin Peng; Juntong Zhang; Yuhao Zhang; Siying Liang; Minghui Zhao; Yongnan Xu; Dongli Li; Yinghua Li (Theriogenology, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

Engineering Escherichia coli to biosynthesize O-polysaccharide-derived recombinant glycoconjugate vaccines against pathogenic serotypes O8 and O9a - Ziyu Li; Guozhen Ma; Ruiying Liu; Xiaohan Wang; Yujie Wang; Xiaojing Zhao; Qing Meng; Lijie Xie; Xiaoya Li; Sijia Liu; Huilin Hao; Xiaolong Jiang; et al. (Carbohydrate Polymers, 2026)

Di-(2-ethylhexyl) terephthalate promotes breast cancer progression: Multi-omics integrated experimental validation - Shiqi Li; Chuyu Zhang; Ye Zhu; Huilin Xie; Liping Chen; Weikang Quan; Jiaqiang Wu; Xianhuan Zhou; Kangping Yang; Liang Yang; Yuan Wei (Chemico-Biological Interactions, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Interactive effects of drought and microplastic particle size on soil bacterial community structure - Yiran Hou; Biao Liu; Jiaying Zhao; Huilin Jia; Luming Zhao; Junfeng Wu; Songya Li; Changrui Zhou (Journal of Hazardous Materials, 2026)

Evaluation of six types of agricultural waste for utilization in sulfate-reducing bioreactors: Batch and continuous-flow operations - Saisai Guo; Yu Wang; Zhipeng Chen; Huilin Li; Mengting Liu; Shanghong Li; Chunrong Wang; Jianbing Wang (Journal of Environmental Management, 2026)

E.coli with surface-displayed Lpp-OmpA-MO2.1 enabling enhanced NO3--N interaction in low C/N wastewater: Performance, anion competition and molecular docking analysis - Huilin Wang; Xiefa Song; Mengli Yao; Zheng Zhou; Zuoliang Sun; Liwei Wang; Jie Li; Dengpan Dong; Meng Li (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Effect of dialysate type on ultrasound-assisted self-assembly Zein nanocomplexes: Fabrication, characterization, and physicochemical stability” [Food Res. Int. 162 (2022) 111812] - Cunshan Zhou; Tong Zhao; Li Chen; Abu ElGasim A. Yagoub; Huilin Chen; Xiaojie Yu (Food Research International, 2026)

Rhubarb-derived extracellular vesicles co-delivered with dexamethasone via multi-layered assembly nanostrategy for targeted ulcerative colitis therapy - Kun Wang; Mengqi Shen; Xu Luo; Lin Li; Ming Wu; Xiaotong Zhang; Huilin Zhu; Qian Du (Chemical Engineering Journal, 2026)

Unlocking the complexity of macromolecular protein heterogeneity of glycoprotein IgE via an optimized online digestion middle-down proteomics approach - Ruijie Liu; Zixin Liang; Shujun Xia; Yuxiang Luo; Huilin Li (Analytica Chimica Acta, 2026)

Development of a TaqMan ‐Based Real‐Time PCR Assay for the Specific Detection of Turbot Circovirus - Huilin Wang; Xia Gao; Ye Gao; Xiaohan Shang; Jie Li (Journal of Fish Diseases, 2026)
Turbot ( Scophthalmus maximus ) is an economically important farming fish in China. Turbot circovirus ( TCV ), a recently discovered member of the Circovirus genus within the Circoviridae family, has emerged as a significant threat to the turbot aquaculture industry in China. This virus is the causative agent of turbot acute hemorrhagic disease ( TAHD ), resulting in substantial economic losses in recent years. As a novel pathogen, the development of more accurate and efficient detection methods for TCV remains an urgent need. In this study, the specific probe and primers were designed based on the consensus sequence of the cap gene of TCV to develop a TaqMan probe‐based real‐time PCR method for virus detection. The specificity of the assay was validated using turbot reddish body iridovirus ( TRBIV ), viral nervous necrosis virus ( VNNV ), the cap gene of European catfish ( Silurus glanis ) circovirus ( CfCV ) and European eel ( Anguilla anguilla ) circovirus ( EeCV ), and no cross‐reaction was observed, indicating the high specificity of the established method. The detection limit of this assay was 10 1 copies per reaction, with an efficiency of 93.7%, a regression squared value of 0.999, and a linear range from 10 1 copies to 10 8 copies of TCV DNA . The assay demonstrated high specificity, sensitivity and reproducibility, with both intra‐ and inter‐assay coefficients of variation less than 2.0%. Then 390 clinical samples suspected of TAHD collected from 2019 to 2022 were tested using this method, and all the samples tested positive for TCV . In this study, we established a TaqMan qPCR ‐based method for TCV detection, which could be applied to epidemiological investigations and pathogenic studies of TCV .

Angelicin attenuates sepsis-associated splenic injury by targeting NF-κB/JAK2/STAT3 and PI3K/Akt pathways to inhibit inflammation and apoptosis - Enzhuang Pan; Huilin Sun; Zhihao Ma; Shasha Zhang; Yedan Liu; Zihan Xu; Yusa Li; Xiaomin Jin; Heng Wang; Jingquan Dong (Toxicology and Applied Pharmacology, 2026)

Energy production is suppressed by vcircRNA_000048- bom-miR-2753-METTL20 regulatory axis in the BmCPV-infected silkworm, Bombyx mori - Huilin Pang; Yuting Li; Min Zhu; Xinyu Tong; Qunnan Qiu; Liuyang Li; Xiaolong Hu; Chengliang Gong; Yunshan Zhang (Insect Biochemistry and Molecular Biology, 2026)

Age-related digestive capacity decline modulates the kinetic patterns of starch and protein digestion from varied diets: An in vitro study - Huilin Shen; Yimeng Shan; Dezhi Li; Kexin Li; Jing Wang; Yue Zhang; Yang Li; Li-Tao Tong (Food Research International, 2026)

Intelligent evaluation of black tea withering quality via image-spectrum fusion using a multimodal attention network with contrastive learning - Qin Ouyang; Huilin Chang; Dengshan Li; Zhenhao Xu; Yuanbin She; Zhonghua Liu (Food Chemistry, 2026)

Exploring the time-regulated fibrillation of chickpea protein isolate: Formation, structural characteristics, and improved functional properties - Shuangshuang Wang; Huilin Lv; Qingshuang Qiu; Zhenzhu Li; Bing Cheng; Jiaying Zhang; Fang Wang; Peifeng Li (Food Hydrocolloids, 2026)

Dual controls on lithospheric dripping: The role of mantle flow and orogen scale - Qiuling Wang; Huilin Wang; Zhuang Li (Earth and Planetary Science Letters, 2026)

Multi-Physics Monitoring of Direct Shear Failure in Submarine Fault Weathered Granite: Characteristics and Precursor Recognition - Jiaqi Li; Zhixiang Liu; Linqi Huang; Xibing Li; Jiangzhan Chen; Huilin Liu (Rock Mechanics and Rock Engineering, 2026)

A smartphone-combined fluorescence sensor based on porous organic polymers for determination of nitrofurans in aquaculture system - Dianwei Zhang; Kexin Li; Li Feng; Hongfei Li; Huilin Liu (Food Chemistry, 2026)

Rapid quantitative real-time analysis and visual detection of Escherichia coli in meat by direct PMAxx-VPCR - Jiaqi Cui; Tingting Zhao; Wenjun Song; Huilin Li; Yan Chen; Rong Chen (Food Control, 2026)

Aqueous phase-stable perovskite quantum dot nanospheres: Synthesis and application for “OFF-ON” fluorescent aptasensing detection of aflatoxin B1 - Xiaochun Hu; Huilin Li; Sujuan Zhang; Mengmeng Gao; Yuan Zhuang; Shuo Wang; Mingfei Pan (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Otomycosis in Southern China: a retrospective analysis of clinical presentation, otoendoscopic features, and causative pathogens - Qiaohui Wang; Dandan Xu; Yiman Li; Yingxuan Zhang; Xuhua Tang; Xianren Wang; Jiande Han; Huilin Su (Mycopathologia, 2026)

Bioactive metabolites from Samsoniella sp. KY1174: isolation, characterization, and cytotoxicity against cancer cell lines - Xingtong Chen; Huiting Wu; Huilin Shu; Haoyu Yu; Fan Cai; Jianbin Xiao; Wei Lin; Yuxin Shi; Mingliang Zhang; Qin Li; Huaidong Zhang; Wanhao Chen; et al. (Natural Product Research, 2026)

Cretaceous–Cenozoic tectonic evolution of the central Qiangtang terrane and implications for the initial growth of the Tibetan Plateau - Xiaohui Liu; Yimin Liu; Ying Rao; Yangrui Guo; Xiaoyu Guo; Xingfu Huang; Huilin Li; Lin Ding; Rui Gao (Tectonophysics, 2026)

Large model-driven physical neural network architecture: Coupled multi-environmental factors for vessel drift trajectory prediction - Fengqi Li; Lingchen Fu; Xuefeng Du; Xin Zhang; Huilin Cheng; Ning Tong; Fengqiang Xu (Ocean Engineering, 2026)

Intracontinental underthrusting and lower crustal duplexing drive the uplift of the Qilian Shan - Huilin Li; Xiaosong Xiong; Xiaoyu Guo; Xingfu Huang; Rui Gao; Jennifer D. Eccles (Gondwana Research, 2026)

Aromatic short peptides: from self-assembled architectures to fluorescent sensing applications in food safety - Dianwei Zhang; Li Feng; Xuecheng Zhu; Hongfei Li; Huilin Liu; Baoguo Sun (Trends in Food Science & Technology, 2025)

Exploring transition pathways to net-zero emissions in China's power sector under different policy portfolios - Yue Wang; Huilin Li; Zhong Wang; Yuyan Luo (Journal of Cleaner Production, 2025)

Photocatalytic activation of peroxyacetic acid by MnFe₂O₄ for efficient caffeine degradation: Efficacy, mechanisms and reusability - Ying Yu; Gengwei Lin; Huilin Dai; Qingsong Li; Chao Huang; Yunbo Song (Journal of Environmental Chemical Engineering, 2025)

Comparative metabolomic analysis of sichuan dishes prepared with animal-based and plant-based meat using an untarxgeted metabolomics approach - Fengyan Liu; Shuyong Shang; Jiaxin Ren; Huilin Zeng; Li Mei (International Journal of Gastronomy and Food Science, 2025)

Quantitative prediction of tertiary formation fractures and its application in lost circulation prediction in the Bozhong Depression - He Du; Jianwei Feng; Shouyu Xu; Junxiao Qu; Chen Li; Xiang Gao; Huilin Xing (Geomechanics for Energy and the Environment, 2025)

Dual mechanisms of Vitisin A in managing alcoholic liver disease: Inhibition of lipogenesis and complement activation - Yuanqin Zhu; Huilin Deng; Jia Liu; Xusheng Li; Xin Huang; Zhaodi Che; Weibin Bai; Rui Jiao (Food and Chemical Toxicology, 2025)

A versatile chitosan hydrogel crosslinked by boronated diol drug conjugates as anti-tumor immune stimulator for hepatocellular carcinoma treatment - Jing Li; Jiaxin Zhao; Jingjia Ye; Fangshen Xu; Sakarie Mustafe Hidig; Lei Zhang; Jie Zhou; Huilin Zheng; Wei Wei; Zhenhua Hu (Carbohydrate Polymers, 2025)

A study on the source parameters and rupture characteristics of the August 6, 2023, MS 5.5 earthquake in pingyuan, Shandong - Shaohui Zhou; Jian Li; Qijie Zhou; Junhao QU; Huilin Wang; Shuang Wu; Yu Wang; Yajun Li (Acta Geodaetica et Geophysica, 2025)

Multi-dimensional fouling process analysis and anti-fouling strategies for catalytic membranes in long-term water treatment - Chenxi Li; Huilin Wan; Xiaojie Qiu; Siyuan Zhai; Peizhe Sun; Yingxin Zhao (Water Research, 2025)

Research on fracturing behavior and mechanism of multi-empty-hole directional blasting in deep hard rock - Huilin Liu; Linqi Huang; Jiangzhan Chen; Zhaowei Wang; Yangchun Wu; Mingjie Li; Xibing Li (Tunnelling and Underground Space Technology, 2025)

Exploring regional carbon emission and power sector transition pathways based on shared socioeconomic pathways: A case study in Sichuan, China - Yue Wang; Huilin Li; Zhong Wang; Yuyan Luo (Journal of Cleaner Production, 2025)

Recent progress in DNA-based approaches for authenticating herbal materials and botanical dietary supplements - Rong Chen; Wenjun Song; Hongling Chen; Tongyi Peng; Huilin Li; Sheng Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Ratiometric fluorescent covalent organic frameworks for rapid detection of nitrofurans in aquatic products - Dianwei Zhang; Kexin Li; Li Feng; Hongfei Li; Charles Q. Jia; Huilin Liu (Food Chemistry, 2025)

The underestimated potential of amorphous covalent organic polymers in electrochromism and energy storage - Keying Feng; Xuehan Wang; Hao Zhang; Huilin Shen; Xiangfu Shi; Zhen Xing; Bolun Wang; Zongjun Li; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2025)

IFNγ-exosomes accelerate wound healing by suppressing immune rejection of allogeneic keratinocytes in collagen/PRP scaffolds via the IDO-kynurenine pathway - Shijie Song; Weidong Zhang; Wei Ji; Ting Li; Kai Guo; Xiang He; Dahai Hu; Huilin Liu; Yunchuan Wang (Chemical Engineering Journal, 2025)

Effect of pulsed magnetic field on the rheological properties, structure, quality attributes of rice starch gel - Jing Wang; Yang Li; Huilin Shen; Jiaxin Li; Yimeng Shan; Mengzi Nie; Ning Li; Yue Zhang; Li-Tao Tong (Carbohydrate Polymers, 2025)

On-site monitoring of atrazine in edible oils: Integrating reverse phase transfer extraction with lateral flow immunoassay for rapid screening - Yulian Wang; Yixue Zhao; Jin Li; Xin Zhao; Jiaxi Liu; Siqi Wang; Huilin Wu; Guoqing Shi (Analytica Chimica Acta, 2025)

On the hotspot-Sun angular offset in urban thermal anisotropy - Wenfeng Zhan; Lu Jiang; Guanwen Chen; Jian Hang; Pan Dong; Shasha Wang; Long Li; Huilin Du (Remote Sensing of Environment, 2025)

A 13-bp insertion in CmAPRR2 gene disrupts its function in regulating the green rind formation of immature melon fruit (Cucumis melo L.) - Liqin Chen; Jing Dong; Zongqing Qiu; Runhua Bu; Yu Zhou; Yuhong Li; Huilin Wang; Liangliang Hu (Plant Science, 2025)

Effect of different vinification processes on chemical and sensory properties of Aronia melanocarpa wines - Qichen Yuan; Zhongzheng Zhang; Mingbo Li; Hailong Xu; Huilin Xiao; Bo Xu; Xu Zhao (Food Research International, 2025)

Fluorescent NH2-MIL-88(Fe)-stabilized PtNPs Nanozyme for Dual-Channel “OFF-ON” simultaneous and visual detection of glyphosate and Pb2+ in Agri-environments and foodstuffs - Huilin Li; Keying Ren; Chunlei He; Xiaochun Hu; Jingming Sun; Shuo Wang; Mingfei Pan (Food Chemistry, 2025)

Co-microencapsulation of Lactobacillus paracasei and Inonotus obliquus polysaccharide in alginate system: Physicochemical and functional properties - Yilin Sun; Jing Han; Huilin Zhang; Wenyan Li; Yujun Jiang; Yu Zhang; Ling Guo (Food Hydrocolloids, 2025)

Dual-regulation of high-valence metals and oxygen vacancy enabled direct electrocatalytic amines oxidation via constructing a M6+-OV-Ni/Co3+ active pocket - Guosheng Wang; Jingzhou Wang; Wenyue Lin; Huilin Li; Haiyang Yu; Xiaohui Liu; Wenjie Zhang; Ying Cao; Xiantai Zhou; Can Xue (Chemical Engineering Journal, 2025)

Non-monotonic effects of soil particle size on UV-assisted electrokinetic remediation of Cr(VI) contaminated soils - Yi Zheng; Yingjun Xie; Zao Jiang; Liang Zhang; Huilin Li; Qiu Yu; Daoping Peng; Yibo Zhang (Journal of Soils and Sediments, 2025)

Highly water-soluble AIEgen for α-amylase activity ultrasensitive detection and ovarian cancer rapid theranostic - Xing Wang; Yuanhang Li; Penglin Wu; Li Yang; Tian Min; Shengnan Yao; Huilin Dong; Zhengjian Qi (Analytica Chimica Acta, 2025)

Convolutional neural networks in the realm of food quality and safety evaluation: Current achievements and future prospects - Jing Zhao; Yue Yu; Siheng Lu; Yue Huang; Xi Yu; Xuejin Mao; Yongjian Yu; Zhanming Li; Huilin Liu (Trends in Food Science & Technology, 2025)

Emerging MXene-based Composites: Synthesis, and Recent Advances in Food Contaminant Analysis - Mengmeng Gao; Rongchao Li; Huilin Li; Xiaochun Hu; Jingming Sun; Hao Wang; Rui Gao; Huilin Liu; Mingfei Pan; Shuo Wang (Trends in Food Science & Technology, 2025)

Performance and mechanism of potassium permanganate activation by percarbonate for enhancing short-chain fatty acid production in the anaerobic fermentation of waste-activated sludge - Zhengjiang Wang; Huilin Luan; Zhenlun Li; Yifan Zeng (Journal of Water Process Engineering, 2025)

Integration of Multi-omics Data Based on Deep Learning for Subtyping of Low-Grade Glioma - Huilin Li; Musu Li; Yue Sun; Er Yu; Jiahe Pan; Yiwen Wu; Zixuan Lu; Hongmei Wo; Fang Shao; Dongfang You; Shaowen Tang; Yang Zhao; et al. (Journal of Molecular Neuroscience, 2025)

Priority protected areas for mangrove conservation in coastal Guangdong, China: Addressing climate and land cover changes - Ruixue Liu; Qixuan Wang; Huilin Kong; Yun Li (Ocean & Coastal Management, 2025)

The effect and mechanism of Fe-modified coffee grounds hydrothermal carbon on the mass transfer efficiency of PMS and H2O2 advanced oxidation - Dahua Yu; Qingdan Liao; Xitong Li; Fumin Liu; Jingxin Huang; Huilin Guan; Yizong Huang (Journal of Water Process Engineering, 2025)

Outer-core size asymmetry and intensification of North Atlantic tropical cyclones - Huilin Li; Xiaodong Tang (Atmospheric Research, 2025)

Review: Nanozyme-based point-of-care testing for portable and on-site monitoring of food contaminants - Huilin Li; Meng Meng; Jing Cao; Xiaochun Hu; Hao Wang; Mingfei Pan; Shuo Wang (Trends in Food Science & Technology, 2025)

Crustal-scale structural and compositional distinction beneath NE Tibet: Evidence from reflection-seismology and Vp/Vs imaging - Huilin Li; Xiaoyu Guo; Zhuo Ye; Xingfu Huang; Hongda Liang; Xiaofan Deng; Xiaomiao Tan; Rui Gao (Lithos, 2025)

Three-dimensional flow characteristics and structures in confluences based on large eddy simulation - Jiao Zhang; Mengmeng Miao; Wen Wang; Zhanbin Li; Peng Li; Huilin Wang; Zi Wu; Binhua Zhao; Jing Li (Journal of Hydrology, 2025)

Unveiling gut microbiota and metabolic functions contributed to polyvinyl chloride degradation in Spodoptera frugiperda larvae - Haoran Peng; Zhe Zhang; Xiaoxi Kang; Yunhua Zhang; Huilin Zhang; Yuxuan Wang; Dongchen Yang; Jinlin Zhang; Yajie Wang; Li Cui; Yong-Guan Zhu; Feng Ju (Journal of Hazardous Materials, 2025)

Deciphering the calcium-binding mechanism of a novel cod bone-derived peptide: A synergistic experimental and computational analysis - Qiaoji Tian; Li Hao; Qian Zhang; Huilin Huang; Chaoxin Tu; Chaozhong Fan; Hu Hou (Food Research International, 2025)

Improving the catalytic activity and thermostability of Mariniflexile fucanivorans fucoidanase by rational design - Huilin Chen; Shengquan Huang; Xiaolan Wang; Mengli Li; Tao Zhang (Food Bioscience, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Trace cobalt accelerates the structural reconstruction to generate high-valence nickel for water-splitting in seawater media - Huilin Zhao; Silu Liu; Fengyuan Tian; Hongdong Li; Liantao Xin; Weiping Xiao; Guangrui Xu; Dehong Chen; Tianyi Ma; Elmurod Egamberdiev; Sardor Donaev; Yingxia Zong; et al. (Chemical Engineering Journal, 2025)

Bioaccessibility and Health Risk Assessment of Arsenic in Realgar-Containing Traditional Chinese Medicines - Jianchao Li; Nuo Deng; Fei Wang; Huilin Zhu; Yongming Li; Xiao Wu (Biological Trace Element Research, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Fluorescent molecularly imprinted hydrogel sensing strip based on nitrogen-doped carbon dots and inverse opal photonic crystals applying for effective detection for imidacloprid in fruits and vegetables - Mingfei Pan; Mengmeng Gao; Jingjing Cui; Rui Gao; Huilin Li; Jingming Sun; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Remote sensing of the oil spills caused by ships: A review - Ming Xie; Ying Li; Zhaoyi Zhang; Qiang Fu; Huilin Jiang (Marine Pollution Bulletin, 2025)

Triploidy induction through cntd1 knockout in red crucian carp (Carassius auratus red var.) - Huilin Li; Yu Zhang; Lina Zhang; Juan Li; Yuan Ou; Ming Wen; Zehong Wei; Jing Wang; Yu Deng; Yinjun Jiang; Conghui Yang; Yuqin Shu; et al. (Aquaculture, 2025)

Global patterns and determinants of year-to-year variations in surface urban heat islands - Xuanqing Guo; Huilin Du; Wenfeng Zhan; Yingying Ji; Chenguang Wang; Chunli Wang; Shuang Ge; Shasha Wang; Jiufeng Li; Sida Jiang; Dazhong Wang; Zihan Liu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Development of an antibacterial hydrogel by κ-carrageenan with carvacrol/hydroxypropyl-β-cyclodextrin composite and its application for strawberry preservation - Huilin Lu; Sai Li; Qunyu Gao (Food Control, 2025)

Oxygen-vacancy-rich Ni/CeO2: UiO-66-derived high-efficiency catalyst for low-temperature CO2 methanation - Yidan Li; Yahui Yang; Zhenzhen Huang; Huilin Zhou; Riying Zeng; Xiaohan Lin; Xiuling Ma; Lihua Wang; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2025)

Multiomics reveals the synergistic response of gut microbiota and spider A. ventricosus to lead and cadmium toxicity - Jinkun Chen; Jing Liu; Shize Liu; Zhongyuan Li; Cuimei Gao; Zhuoman Wang; Siqi Huang; Zijian Jiang; Huilin Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Anthill-Inspired bionic bone cement enhances bone regeneration by guiding angiogenesis and regulating BMSCs metabolism with anti-ROS capacity - Chen Qian; Gaoran Ge; Haifu Sun; Xiaoqin Yang; Yi Qin; Wenhao Li; Wentie Yang; Xuequan Zhao; Ye Gu; Yusen Qiao; Dechun Geng; Huilin Yang (Chemical Engineering Journal, 2025)

In-situ surface reconstruction of BiVO4/CuFe2O4 photoanode for efficient and robust solar water oxidation - Tengfei Wang; Kai Song; Houjiang Liu; Hongyan Li; Yufei Zhang; Weijie Ren; Rui Zhang; Kun Li; Fang He; Zhenxing Qin; Huilin Hou (Chemical Engineering Journal, 2025)

Optimization of Microsatellite Multiplex PCRs for Triploidy Verification and Genetic Diversity Assessment in the Pacific Oyster, Crassostrea gigas - Huilin Zheng; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Wenlong Bi; Hong Hu; Qi Li (Marine Biotechnology, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Patterns and drivers of surface cooling effect of urban trees across global cities - Jiarui Li; Shasha Wang; Wenfeng Zhan; Jiufeng Li; Huilin Du; Long Li; Chunli Wang; Yingying Ji (Science of The Total Environment, 2025)

Assessment of instantaneous sampling on quantifying satellite-derived surface urban heat islands: Biases and driving factors - Zihan Liu; Wenfeng Zhan; Yanlan Wu; Jiufeng Li; Huilin Du; Long Li; Shasha Wang; Chunli Wang (Remote Sensing of Environment, 2025)

Comprehensive assessments of a diagnostic equation for estimating diurnally maximum canopy urban heat island intensity - Yihan Gao; Wenfeng Zhan; Huilin Du; Chenguang Wang; Shasha Wang; Yingying Ji; Shuang Ge; Chunli Wang; Jiufeng Li (Building and Environment, 2025)

Damage distribution characteristics and space optimizations of the large-diameter deep multi-holes blasting in thick ore bodies - Huang Linqi; Wang Zhaowei; Liu Kai; Liu Huilin; Li MingJie; Shen Huiming; Li Xibing (Tunnelling and Underground Space Technology, 2025)

A novel pore-scale simulation method for viscoplastic multiphase fluid flow regulation using nanocomposite fluids in heterogeneous porous media - Yue Li; Bin Yuan; Can Ke; Wei Zhang; Huilin Hou (Chemical Engineering Journal, 2025)

From plankton to fish: The multifaceted threat of microplastics in freshwater environments - Cuimei Gao; Baohong Xu; Zhongyuan Li; Zhuoman Wang; Siqi Huang; Zijian Jiang; Xiaomin Gong; Huilin Yang (Aquatic Toxicology, 2025)

Baihu Jia Renshen Decoction may improve skeletal muscle and adipose tissue functions of type I diabetic rats by affecting pancreatic β-cell function - Shufang Chu; Deliang Liu; Hengxia Zhao; Ling Liu; Juntong Li; Gaoxiang Wang; Xuemei Liu; Huilin Li (Genes & Genomics, 2025)
Background Baihu Jia Renshen Decoction (BJRD) is used for diabetes mellitus (DM) management in clinics. Objective To elucidate the potential mechanism of BJRD in treating type 1 DM (T1DM). Methods T1DM models were established via intraperitoneal injection of streptozotocin (STZ). Rats were subsequently randomly divided into the normal control (NC), model (MOD), insulin (INS), INS + BJRD-medium dose (MID), and INS + BJRD-high dose (HIGH) groups. The rats’ body weight was measured. Transcriptome sequencing was performed to detect differentially expressed genes (DEGs) in the muscle and adipose tissues. Quantitative real-time polymerase chain reaction was utilized to verify the DEG levels. Results Body weights of MOD, INS, MID, and HIGH groups were significantly reduced as compared to those of NC group. Compared with NC group, MOD group showed significant Hspa1b and Notch3 downregulation and Camkk2 level elevation. Compared with MOD group, INS group showed further downregulation of the Hspa1b level, whereas MID group exhibited an increase. The Camkk2 levels in INS, MID, and HIGH groups were further reduced. The Notch3 levels did not significantly change in INS and MID groups, whereas that of HIGH group increased. Additionally, compared with NC group, MOD group demonstrated upregulation of the Myl1, Mylpf, Acacb, and Pygm levels and downregulation of Fasn level. Compared with MOD group, Myl1, Mylpf, and Pygm levels in INS, MID, and HIGH groups were down-regulated, whereas Fasn and Acacb levels were up-regulated. Conclusion BJRD may influence pancreatic β-cell function, thereby enhancing the function of the skeletal muscle and adipose tissues in a T1DM rat model.

Identification of a novel circovirus associated with turbot (Scophthalmus maximus) acute hemorrhage disease - Jingzhe Jiang; Huilin Wang; Liming Xu; Yong Zhou; Qiwei Qin; Qiyao Wang; Zhihui Huang; Jingguang Wei; Zhizhong Xiao; Jie Li (Aquaculture, 2025)

Intelligent electronic components waste detection in complex occlusion environments based on the focusing dynamic channel-you only look once model - Huilin Liu; Yu Jiang; Wenkang Zhang; Yan Li; Wanqi Ma (Journal of Cleaner Production, 2025)

Rational design of high-entropy P2/O3 biphasic layered cathodes for enhanced sodium storage performance - Yanfen Wen; Chungang Lin; Hao Shen; Kai Fang; Fupeng Li; Chengkui Luo; Xiaolin Wang; Huilin Peng; Yu Qiao; Shuxin Zhuang; Mi Lu (Chemical Engineering Journal, 2025)

Fenofibrate induces liver enlargement in aging mice via activating the PPARα-YAP signaling pathway - Huilin Li; Yanying Zhou; Chenghui Cai; Hangfei Liang; Xuan Li; Min Huang; Shicheng Fan; Huichang Bi (Chemico-Biological Interactions, 2025)

Effect of Flame Jet-Induced Damage on Physical and Mechanical Properties of Granite - Yangchun Wu; Linqi Huang; Huilin Liu; Xibing Li (Rock Mechanics and Rock Engineering, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

Impact of elevated CO2 on microbial communities and functions in riparian sediments: Role of pollution levels in modulating effects - Ziyu Li; Dapeng Li; Songqi Liu; Huilin Zhao; Boling Li; Sujie Shan; Yizhi Zhu; Jingqiu Sun; Jun Hou (Science of The Total Environment, 2024)

Recent insights into anthocyanin biosynthesis, gene involvement, distribution regulation, and domestication process in rice (Oryza sativa L.) - Taotao Zhu; Mengxue Du; Huilin Chen; Gang Li; Mengping Wang; Lingzhi Meng (Plant Science, 2024)

Construction of a sulfonic acid functionalized hypercrosslinked polymer for the adsorption of rubidium and cesium - Yang Wang; Lulu Zhang; Shuli Wang; Huilin Feng; Feifei Pang; Haolin Li; Bohan Liu; Xiaohuan Zang; Shuaihua Zhang; Zhi Wang (Journal of Water Process Engineering, 2024)

Fungal communities in three root herbs: Insights and implications - Yanan Xu; Chune Fan; Huilin Yuan; Yufeng Li; Jianping Han; Meihua Yang; Xiaohui Pang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Analysis of structural composition and antioxidant activity of traditional fermented sour meat peptides - Dezhen Meng; Lijun Zhao; Yaodi Zhu; Lingxia Sun; Miaoyun Li; Huilin Wu; Dong Liang; Yanxia Liu; Yangyang Ma; Gaiming Zhao; Shijie Liu (Food Chemistry, 2024)

Epidemiological survey of 32,786 culture-positive dermatophytosis cases in Hangzhou from 2018 to 2023 - Qiuping Li; Jiajia Li; Huilin Zhi; Wenwen Lv; Bo Sang; Yan Zhong; Xiaoyu Chen; Xiujiao Xia; Zehu Liu (Mycopathologia, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Crustal-scale architecture and origin of the Haiyuan Arcuate Tectonic Belt, NE Tibet - Zizhao Yuan; Yanqi Lin; Xiao Xu; Huilin Li; Xiaoyu Guo; Chunsen Li; Xiaofei Tong (Tectonophysics, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

High-resolution satellite estimates of coal mine methane emissions from local to regional scales in Shanxi, China - Shengxi Bai; Yongguang Zhang; Fei Li; Yingqi Yan; Huilin Chen; Shuzhuang Feng; Fei Jiang; Shiwei Sun; Zhongting Wang; Chunyan Zhou; Wei Zhou; Shaohua Zhao (Science of The Total Environment, 2024)

3D printing for constructing biocarriers using sodium alginate/ε-poly-l-lysine ink: Enhancing microbial enrichment for efficient nitrogen removal in wastewater - Yinuo Liu; Huilin Wan; Jiaojiao Niu; Minghao Zhao; Wei Shang; Pengfeng Li; Jiaju Li; Yue Zhang; Zuodong Wu; Yingxin Zhao (Science of The Total Environment, 2024)

Lattice matched Z-scheme ZnIn2S4/Ag3PO4 enhanced photocatalytic performance by controlling morphology synthesis - Zhenyu Fu; Kai Ye; Zhenyou Dong; Suyun Li; Huilin Zhou; Sihang Xia; Longxiang Shen; Wenyan Shi (Journal of Environmental Chemical Engineering, 2024)

Fraction-dependent variations in cooling efficiency of urban trees across global cities - Wenfeng Zhan; Chunli Wang; Shasha Wang; Long Li; Yingying Ji; Huilin Du; Fan Huang; Sida Jiang; Zihan Liu; Huyan Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Experimental study on dynamic response of hard rock blasting under in-situ stress - Huilin Liu; Linqi Huang; Zhaowei Wang; Yangchun Wu; Xibing Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

A novel thermo-responsive phospholipase A1 with high selectivity and efficiency in enzymatic oil degumming - Zhong Li; Huilin Zhou; Xuan Liu; Weifei Wang; Dongming Lan; Yonghua Wang (Food Chemistry, 2024)

A smartphone-combined ratiometric fluorescence molecularly imprinted probe based on biomass-derived carbon dots for determination of tyramine in fermented meat products - Dianwei Zhang; Yuhua Zhang; Kexin Li; Shengnan Wang; Yuanchen Ma; Yonghong Liao; Fenghuan Wang; Huilin Liu (Food Chemistry, 2024)

Effect of fermentation with single and co-culture of lactic acid bacteria on Chinese Elaeagnus angustifolia juice: Evaluation of bioactive compounds and volatile profiles - Chang Chen; HuiLin Li; YunPing Zhu; YaWen Zhou; QingHong Luo (Food Bioscience, 2024)

Natural insect-derived Nanoparticle: An ultra-bright and instantaneous Labeled signal tag for green and efficient Immunochromatographic assay of chloramphenicol - Shaochi Wang; Ting Du; Huilin Jia; Wentao Zhang; Jing Sun; Daohong Zhang; Zhenyu Li; Jie Cheng; Jianlong Wang (Chemical Engineering Journal, 2024)

Spermidine protects cartilage from IL-1β-mediated ferroptosis - Qi Cheng; Li Ni; Ang Liu; Xiaoxiong Huang; Pan Xiang; Qin Zhang; Huilin Yang (Molecular and Cellular Biochemistry, 2024)

Morphology and Texture-Guided Deep Neural Network for Intracranial Aneurysm Segmentation in 3D TOF-MRA - Maysam Orouskhani; Negar Firoozeh; Huayu Wang; Yan Wang; Hanrui Shi; Weijing Li; Beibei Sun; Jianjian Zhang; Xiao Li; Huilin Zhao; Mahmud Mossa-Basha; Jenq-Neng Hwang; et al. (Neuroinformatics, 2024)

Detection of 6-PPD and 6-PPDQ in airborne particulates and assessment of their toxicity in lung cells - Huilin Chen; Maomao Xie; Wenjie Li; Lipin Tan; Xiaoming Cai; Mingjing Shen; Ruibin Li (Chemosphere, 2024)

Three-birds-with-one-stone: An eco-friendly and renewable humic acid-derived material application strategy for macrolide antibiotic detection and multifunctional composite film preparation - Peiqi Li; Siyu Hou; Yuqi Zhang; Kaidi Zhang; Xiqian Deng; Huilin Song; Guowen Qin; Yang Zheng; Wenyuan Liu; Shunli Ji (Journal of Hazardous Materials, 2024)

Amorphous W-doped iron phosphide with superhydrophilic surface to boost water-splitting under large current density - Silu Liu; Yue Wang; Huilin Zhao; Hongdong Li; Weiping Xiao; Zhenyu Xiao; Guangrui Xu; Dehong Chen; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2024)

Enzyme induced polymer degradation as a pathway to create microbial habitats for biomanufacturing intensification - Wei Cheng; Huilin Wen; Haixia Shen; Chenwei Fu; Erkuang Miao; Dongbao Li; Xiaoqiang Chen; Chi Hu; Ziyi Yu (Chemical Engineering Journal, 2024)

Sandwich-structured continuous ZIF-8/Ti3C2 MXene/ZIF-8 for efficient sterilization: Enhanced photocatalytic activity, photothermal effect, and environmental safety - Furong Xiong; Huilin Hu; Xiang Xue; Minqi Wu; Jiajie Zhou; Wang Zhang; Rui Li (Water Research, 2024)

The protective effects of Kefir extract (KE) on intestinal damage in larval zebrafish induced by Oxytetracycline: Insights into intestinal function, morphology, and molecular mechanisms - Yang Qiu; Fujie Yan; Huilin Yu; Honghao Li; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Research International, 2024)

Tree species mixing effects on the radial growth of Pinus massoniana and Castanopsis hystrix: A comparison between even-aged and uneven-aged stands - Renjie Chen; Xiali Guo; Yuxian Ge; Qidong Li; Angang Ming; Huilin Min; Weijun Shen (Forest Ecology and Management, 2024)

Graphite-N reinforced sludge biochar electrode: A experimental and DFT theoretical analysis of efficient evolution and in-situ utilization of H2O2 - Chenxi Li; Xiaojie Qiu; Huilin Wan; Zehao Ma; Ruotong Jin; Yingxin Zhao (Environmental Pollution, 2024)

Weekly rhythms of urban heat islands: A multicity perspective - Huilin Du; Wenfeng Zhan; Zihan Liu; Chunli Wang; Shasha Wang; Long Li; Jiufeng Li; Benjamin Bechtel; Panagiotis Sismanidis (Sustainable Cities and Society, 2024)

Microfluidic paper-based analysis device applying black phosphorus nanosheets@MWCNTs-COOH: A portable and efficient strategy for detection of β-Lactoglobulin in dairy products - Xintong Han; Dan Zhang; Mengjiao Xie; Jingying Yang; Yueyao Wang; Huilin Li; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Bimetallic Ag/Au nanoclusters encapsulated in ZIF-8 framework: A novel strategy for ratiometric fluorescence detection of doxycycline in food - Yueyao Wang; Mengmeng Gao; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Dewatering and valorizing lake sediments by electroosmotic dewatering for lakes restoration - Huilin Li; Lisbeth M. Ottosen (Environmental Science and Pollution Research, 2024)
Dredging eutrophic lake sediments can improve water quality, but it also requires dewatering and valorizing the dredged material to avoid wasting resources like phosphorus. This study experimentally investigated the basic mechanism and performance of electroosmotic dewatering of 1-L dredged sediments using different electric currents (20 mA, 40 mA, and 60 mA) after gravity filtration. The dewatering performance, moisture content and distribution, effect of electrochemical reaction on dewaterability, energy consumption, and changes in metals and phosphorus (P) distribution and pH values were analyzed. The results indicated that electroosmotic dewatering effectively decreased sediment mass by predominantly eliminating free and a portion of interstitial water, with reductions ranging from 7 to 20%. The optimal duration and current should, however, be considered to balance water removal and energy consumption. Higher moisture removal occurred with 40 mA for 24 h and 60 mA for 6 h, while the energy consumption obtained with 60 mA (0.201 kWh/kg water removed ) was significantly lower than that of applying 40 mA for 24 h (0.473 kWh/kg water removed ), with the assistance of ohmic heating, resulting in reduced viscosity and water release from capillaries. The tested conditions did not significantly extract heavy metals or P from the sediments, which may facilitate the disposal of the removed water back into the lake and the utilization of the treated sediments for different purposes. This technology is easy to operate and suitable for the treatment of dredged sediments, and the dewatering result is comparable to low pressurized filtration but at low energy consumption.

The reversal of PXR or PPARα activation-induced hepatomegaly - Yifei Zhang; Jie Yang; Shicheng Fan; Yue Gao; Chenghui Cai; Huilin Li; Xuan Li; Xiao Yang; Yunhui Xing; Min Huang; Huichang Bi (Toxicology Letters, 2024)

Genome-wide identification of thaumatin-like protein family genes in Panax notoginseng and analysis of their responses to Fusarium solani infection - Yun Yang; Huilin Guan; Fugang Wei; Zecheng Li; Shaozhou Yang; Jingxin Huang (Genetic Resources and Crop Evolution, 2024)

Response of a source water quality through a heavy precipitation event: Nutrients, dissolved organic matter and their DBPs formation - Yujin Yuan; Xinrui Liang; Qingsong Li; Jing Deng; Jing Zou; Guoxin Li; Guoyuan Chen; Wenjie Qin; Huilin Dai (Journal of Cleaner Production, 2024)

Effects of calcium chloride on the gelling and digestive characteristics of myofibrillar protein in Litopenaeus vannamei - Kexin Zhang; Yefan Wang; Xin Fan; Na Li; Zhifeng Tan; Huilin Liu; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2024)

Multiple-state pattern encrypted superhydrophobic-icephobic colorimetric sensing film for anticounterfeiting and food freshness monitoring - Huilin Dong; Xiaoya Sun; Haichao Li; Deqiang Li; Zhe Ling; Sheng Chen; Yanglei Xu; Feng Xu (Chemical Engineering Journal, 2024)

Excellent energy storage performance of lead-based antiferroelectric ceramics via enhancing dielectric breakdown mechanism - Jian Zhou; Zisheng Xu; Huilin Yang; Limin Chu; Liming Chen; Hangren Li; Jianxiang Ding; Songlin Ran; Zhengming Sun; Xihong Hao (Chemical Engineering Journal, 2024)

A Rapid Reconstruction Method of 3D Digital Rock with Strong Pore Connectivity - Weichao Yan; Naser Golsanami; Huilin Xing; Sanzhong Li; Peng Chi (Pure and Applied Geophysics, 2024)

Unraveling the influence of biogenic volatile organic compounds and their constituents on ozone and SOA formation within the Yellow River Basin, China - Jiale Yong; Yuanli Xie; Huilin Guo; Yunmei Li; Shaoqi Sun (Chemosphere, 2024)

Effect of konjac glucomannan on gelling and digestive properties of myofibrillar protein in Litopenaeus vannamei based on molecular docking - Deyang Li; Na Li; Yefan Wang; Kexin Zhang; Zhifeng Tan; Huilin Liu; Xiaoyang Liu; Qiong Wu; Dayong Zhou (Food Hydrocolloids, 2024)

Delivering cells via ECM mimetic hydrogel microspheres for promoting the reconstruction of rat lumbar nucleus pulposus - Hao Liu; Xin Tian; Chenyang Jin; Yangfeng Li; Xuesong Zhu; Ming Pei; Tao Liu; Huilin Yang; Yong Xu; Fan He (Chemical Engineering Journal, 2024)

Exploring the combined cooling effect of street canyon geometry and the surrounding built environment - Ziyi Liu; Lihui Hu; Huilin Chen; Zexun Li; Ling Jiang (Environmental Science and Pollution Research, 2024)

Response mechanism of soil leachate and disinfection by-product formation to extreme precipitation events under continuous drought scenario - Yujin Yuan; Qingsong Li; Jing Deng; Xiaoyan Ma; Xiaobin Liao; Jing Zou; Jie Liao; Huahan Huang; Huilin Dai (Science of The Total Environment, 2024)

Rapid colorimetric and fluorescence identification of Pinelliae Rhizoma and adulterate Rhizoma Typhonii Flagelliformis using direct-LAMP assay - Huilin Li; Jiaqi Cui; Hongling Chen; Hongying Li; Yuchen Xie; Wenjun Song; Rong Chen (Food Chemistry, 2024)

Chemical Cues Released by Predators’ Consumption of Heterospecific Prey Alter the Embryogenesis of Zebrafish - Ainuo Lin; Yaxi Li; Zhi Yan; Huilin Zhang; Baozhen Jiang; Jingjing Chen; Derui Wang; Huan Wang; Xiaodong Li; Zhen Lu; Ke Li (Fishes, 2024)
Environmentally cued hatching is prevalent, diverse, and crucial to many animals’ survival. Fish embryos use a variety of chemical cues to initiate hatching to avoid potential predators, yet the function of chemical cues released from the predatory consumption of heterospecific prey is largely unknown. Zebra cichlids (Metriaclima estherae) are ferocious predators that can feed on medaka (Oryzias latipes), though it is impossible for this to occur in their natural habitat. Zebrafish (Danio rerio) embryos have been employed as experimental subjects due to their sensitivity to a variety of chemical signals. In this study, zebrafish embryos were subjected to three types of chemical signals: predator cues (PCs, released from cichlids), heterospecific cues (HCs, released from medaka), and heterospecific dietary cues (HDCs, released from cichlids that have ingested medaka). As a result, the hatching times of zebrafish embryos were accelerated by 6.8% and 12.6% by PCs and HDCs, respectively. PCs and HDCs cause significantly reduced morphology in zebrafish embryos, including regarding total length, eye length, dorsal fin length, trunk height, caudal fin height, and body cavity, and increase yolk sac height. The PCs and HDCs diminished the larvae’s motion at 120 and 144 h post fertilization (hpf), which could be attributed to non-developmental embryogenesis. Overall, the impacts of HDCs on embryonic hatching, developmental morphology, and locomotor were more pronounced in comparison with PCs. Our findings demonstrate that predators’ dietary cues, even those released after predation on heterospecific prey, can modify embryogenesis, highlighting the critical functions of chemical signals in predation risk assessment using embryos.

Carbon dots-based fluorescent molecularly imprinted photonic crystal hydrogel strip: Portable and efficient strategy for selective detection of tetracycline in foods of animal origin - Mingfei Pan; Yueyao Wang; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang (Food Chemistry, 2024)

Magnetic-fluorescent immunosensing platform applying AuNPs heterogeneous MIL-53(Al) composite for efficient detection of zearalenone - Huilin Li; Jingying Yang; Ran Han; Yueyao Wang; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Ultrasound-mediated multifunctional magnetic microbubbles for drug delivery of celastrol in VX2 liver transplant tumors - Jian Huang; Zhengji Wang; Zihe Chen; Chunxin Huang; Ying Wang; Xing Li; Weiyang Lv; Guiqiang Qi; Huilin Liu (Drug Delivery and Translational Research, 2024)

Rainwater extracting characteristics and its potential impact on DBPs generation: A case study - Yujin Yuan; Qingsong Li; Jing Deng; Xiaoyan Ma; Xiaobin Liao; Jing Zou; Guoxin Li; Guoyuan Chen; Huilin Dai (Science of The Total Environment, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

Native top-down mass spectrometry for monitoring the rapid chymotrypsin catalyzed hydrolysis reaction - Yujia Ying; Huilin Li (Analytica Chimica Acta, 2024)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Simple yet efficient downscaling of land surface temperatures by suitably integrating kernel- and fusion-based methods - Pan Dong; Wenfeng Zhan; Chenguang Wang; Sida Jiang; Huilin Du; Zihan Liu; Yangyi Chen; Long Li; Shasha Wang; Yingying Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of cooling methods on mechanical behaviors and thermal damage distributions of granite: Experiments and simulations - Yangchun Wu; Linqi Huang; Xibing Li; Yide Guo; Huilin Liu; Jiajun Wang (Geothermics, 2023)

Development of a trace quantitative method to investigate caffeine distribution in the Yellow and Bohai Seas, China, and assessment of its potential neurotoxic effect on fish larvae - Zhi Yan; Yaxi Li; Ainuo Lin; Xiao Yang; Zhen Lu; Huilin Zhang; Jianhui Tang; Jianmin Zhao; Donglei Niu; Tianyu Zhang; Xiaodong Zhao; Ke Li (Marine Pollution Bulletin, 2023)

Mechanical properties and failure characteristics of anisotropic shale with circular hole under combined dynamic and static loading - Huilin Liu; Xianhui Feng; Liyuan Liu; Tianjiao Li; Chunan Tang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Triassic convergence and tectonic evolution of the West Qinling orogen: Constraints from reflection-seismology imaging - Huilin Li; Rui Gao; Xingfu Huang; Haiyan Wang; Xiaoyu Guo; Hongda Liang; Xiaomiao Tan; Xiaohui Liu; Zhen Yang (Gondwana Research, 2023)

Portable smartphone-assisted fluorescence-colorimetric multidimensional immunosensing microarray based on NH2-UiO-66@PtNPs multifunctional composite for efficient and visual detection of amantadine - Huilin Li; Jingying Yang; Xiaochun Hu; Ran Han; Shuo Wang; Mingfei Pan (Chemical Engineering Journal, 2023)

Urban heat islands characterized by six thermal indicators - Chenguang Wang; Wenfeng Zhan; Long Li; Shasha Wang; Chunli Wang; Shiqi Miao; Huilin Du; Lu Jiang; Sida Jiang (Building and Environment, 2023)

Assessment of heavy metal pollution and preschool children health risk in urban street dusts from different functional areas in a typical industrial and mining city, NW China - Jinglei Zhang; Huilin Gu; Shun Chen; Weichang Ai; Yuhui Dang; Shiwei Ai; Zhilan Li (Environmental Geochemistry and Health, 2023)

Correction to: Integrative analysis of genes reveals endoplasmic reticulum stress-related immune responses involved in dilated cardiomyopathy with fibrosis - Wanpeng Li; Peiling Liu; Huilin Liu; Fuchun Zhang; Yicheng Fu (Apoptosis, 2023)

Integrative analysis of genes reveals endoplasmic reticulum stress-related immune responses involved in dilated cardiomyopathy with fibrosis - Wanpeng Li; Peiling Liu; Huilin Liu; Fuchun Zhang; Yicheng Fu (Apoptosis, 2023)
Endoplasmic reticulum (ER) stress has been implicated in the mechanisms underlying the fibrotic process in dilated cardiomyopathy (DCM) and results in disease exacerbation; however, the molecular details of this mechanism remain unclear. Through microarray and bioinformatic analyses, we explored genetic alterations in myocardial fibrosis (MF) and identified potential biomarkers related to ER stress. We integrated two public microarray datasets, including 19 DCM and 16 control samples, and comprehensively analyzed differential expression, biological functions, molecular interactions, and immune infiltration levels. The immune cell signatures suggest that inflammatory immune imbalance may promote MF progression. Both innate and adaptive immunity are involved in MF development, and T-cell subsets account for a considerable proportion of immune infiltration. The immune subtypes were further compared, and 103 differentially expressed ER stress-related genes were identified. These genes were mainly enriched in neuronal apoptosis, protein modification, oxidative stress reaction, glycolysis and gluconeogenesis, and NOD-like receptor signaling pathways. Furthermore, the 15 highest-scoring core genes were identified. Seven hub genes ( AK1 , ARPC3 , GSN , KPNA2 , PARP1 , PFKL , and PRKC ) might participate in immune-related mechanisms. Our results offer a new integrative view of the pathways and interaction networks of ER stress-related genes and provide guidance for developing novel therapeutic strategies for MF.

Divergent urbanization-induced impacts on global surface urban heat island trends since 1980s - Long Li; Wenfeng Zhan; Leiqiu Hu; TC Chakraborty; Zhihua Wang; Peng Fu; Dazhong Wang; Weilin Liao; Fan Huang; Huyan Fu; Jiufeng Li; Zihan Liu; et al. (Remote Sensing of Environment, 2023)

Punicalagin alleviates the hyperproliferation of keratinocytes in psoriasis through inhibiting SKP2 expression - Lipeng Tang; Bowen Zhang; Guanzhuo Li; Ying Zhu; Bing Feng; Zuqing Su; Wenhui Han; Huilin Huang; Qiuping Li; Maojie Wang; Yuchao Chen; Huazhen Liu; et al. (Journal of Natural Medicines, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Health risk assessment of lead via the ingestion pathway for preschool children in a typical heavy metal polluted area - Yue Du; Shiwei Ai; Jie He; Huilin Gu; Xiaoxue Wang; Zhilan Li; Yuhui Dang (Environmental Geochemistry and Health, 2023)

Study on uniaxial compressive strength of double matrix bimrocks considering different block proportions - Kai Li; Shaorui Sun; Huilin Le; Jihong Wei; Yanran Hu (Bulletin of Engineering Geology and the Environment, 2023)

Association between greenspace and cancer: evidence from a systematic review and meta-analysis of multiple large cohort studies - Jiang Li; Yafei Xie; Jianguo Xu; Chun Zhang; Huilin Wang; Danqi Huang; Guoqiang Li; Jinhui Tian (Environmental Science and Pollution Research, 2023)

Two new triterpene glycosides with antiproliferative activities on HepG2 from Phytolacca acinosa fruit fermentation broth - Biao Li; Yuxing Wang; Changfu Wang; Donghui Peng; Huilin Su; Congjing Shi; Wenlong Liu; Haixue Kuang; Qiuhong Wang (Natural Product Research, 2023)

Novel antiosteoporotic peptides purified from protein hydrolysates of taihe black-boned silky fowl: By larval zebrafish model and molecular docking - Yang Qiu; Jianyue Ying; Fujie Yan; Huilin Yu; Yan Zhao; Honghao Li; Shengyao Xia; Jianchu Chen; Jiajin Zhu (Food Research International, 2023)

Review: Synthesis of metal organic framework-based composites for application as immunosensors in food safety - Mingfei Pan; Huilin Li; Jingying Yang; Yixin Wang; Yueyao Wang; Xintong Han; Shuo Wang (Analytica Chimica Acta, 2023)

Expression and interaction analysis between BjuLKP2 and BjuPP2C52 in B. juncea - Anran Wu; Huilin Tan; Liang Zhao; Shizhe Jiang; Yiping Wu; Yushan Tao; Mengyao Wang; Mengtao Sheng; Xiuyu Zhao; Li Feng; Meiping Quan; Jing Zeng (South African Journal of Botany, 2023)

A green and facile one-step hydration method based on ZIF-8-PDA to prepare melamine composite sponges with excellent hydrophobicity for oil-water separation - Yuqi Zhang; Siyu Hou; Huilin Song; Guowen Qin; Peiqi Li; Kaidi Zhang; Tengfei Li; Lingfei Han; Wenyuan Liu; Shunli Ji (Journal of Hazardous Materials, 2023)

A novel electric spark precipitation and electrospinning strategy to prepare cerium hydroxide nanocomposite for phosphate uptake from aqueous solutions - Yanbo Zeng; Yuanxin Li; Xiuxiu Jia; Guangzhi Hu; Huilin Bi; Xiaopeng Zhang; Bin Du; Fengqin Chang (Journal of Environmental Chemical Engineering, 2023)

A multiple-fluids-mechanics-based model of velocity profiles in currents with submerged vegetation - Jiao Zhang; Zhangyi Mi; Huilin Wang; Wen Wang; Zhanbin Li; Muhong Guan (Frontiers in Marine Science, 2023)
Submerged aquatic vegetation can provide a habitat and food for marine and river organisms, and it has the ecological effect of purifying water by absorbing harmful substances. Therefore, it plays an important role in the maintenance, restoration, and improvement of marine and river ecosystems. Hydrodynamic problems caused by submerged vegetation have been a matter of wide concern. According to the distribution of submerged vegetation, the flow can be divided into three layers in the vertical direction: uniform, mixing, and logarithmic layers. This paper proposes an analytical model for the vertical distribution of longitudinal velocity in open-channel flows with submerged vegetation. A concept of velocity superimposition is applied in mixing and logarithmic layers. The velocity inside the vegetated layer can be solved by the balance between the drag force and bed gradient. The velocity difference between the vegetated layer and the free surface layer results in the formation of a mixing layer near the top of the vegetation. Flow at the junction between the vegetation and free surface layers is mainly controlled by the vortices in the mixing layer. The velocity in the mixing layer is commonly described by a hyperbolic tangent formula. The logarithmic distribution formula is applied to the free surface layer, where the velocity without effect arising from vortices is similar to the open-channel flow. The concept of the wake function is introduced to modify the distribution of velocity in the free surface layer. The longitudinal velocities from the theoretical model are compared to the measured velocities in the literature. The theoretical velocities agree well with the measured values in the flows with submerged vegetation, proving that the theoretical model proposed here can successfully predict the vertical distribution of velocity and has extensive adaptability.

Effect of E-beam irradiation on the qualitative attributes of shrimp (Penaeus vannamei) - Yan Zhao; Huilin Yu; Honghao Li; Yang Qiu; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Bioscience, 2023)

LncRNA PVT1 upregulates FBN1 by sponging miR-30b-5p to aggravate pulpitis - Yuanyuan Li; Shuangshuang Li; Ruijing Li; Huilin Xu (Molecular & Cellular Toxicology, 2023)

Epidemiology of turbot bacterial diseases in China between October 2016 and December 2019 - Ye Gao; Qiyao Wang; Yaokuan Liu; Yue Ma; Huaiyuan Jin; Jingjing Liu; Huilin Wang; Yongwei Yan; Jie Li (Frontiers in Marine Science, 2023)
Turbot ( Scophthalmus maximus ) is an important commercial fish in China that can be infected by a series of bacterial pathogens, leading to great economic losses. In this study we focused on the epidemiology of turbot bacterial diseases in the major farming areas in China for three years. A total of 155 cases with 446 diseased turbots were investigated, and dominant bacterial pathogens were isolated from 137 cases (344 turbots). Thus, bacteria are the major threat to farming turbot in China. Edwardsiella piscicida was the major pathogen, which isolated as the dominant colony in 62 cases (40.00%) with 151 turbots (33.85%). Aeromonas salmonicida was isolated in 57 cases (36.77%) with 116 turbots (26.01%). Vibrio anguillarum was isolated in nine cases (5.81%), and Streptococcus parauberis in five cases (3.23%). Photobacterium damselae and Mycobacterium marinum were also isolated from one or two diseased fish. Other Vibrio spp. were isolated in 15 cases (9.68%). Two species of pathogen were isolated in 13 cases, and three species ( E. piscicida , A . salmonicida , and S . parauberis ) in one case. In 19 cases, no bacteria were isolated. Based on the annual disease analysis, we found that the E . piscicida infection proportion of total cases was greatly decreased, which may be caused by the attenuated vaccine inoculated in 2018. The antibiotic resistance of E . piscicida strains isolated in Weifang city was also determined. We found that the resistance to ceftriaxone, doxycycline, and SMZ/TMP were significantly increased from October 2016 to June 2018, and all the E . piscicida isolates exhibited resistance to SMZ/TMP in June 2018. These results indicated that E . piscicida is the major threat to turbot farming in China, and the attenuated E . piscicida vaccine exhibits effective protection. The usage of antibiotics may induce resistance quickly. Thus, development of vaccines is an important work for sustainable development of turbot farming in the future.

Tomographic evidences for hydraulic fracturing induced seismicity in the Changning shale gas field, southern Sichuan Basin, China - Yuyang Tan; Jiawei Qian; Jun Hu; Haijiang Zhang; Huilin Xing; Junlun Li; Jian Xu; Wen Yang; Ning Gu; Siyu Miao (Earth and Planetary Science Letters, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

β-catenin/TCF4 inhibitors ICG-001 and LF3 alleviate BDL-induced liver fibrosis by suppressing LECT2 signaling - Yue Gao; Shicheng Fan; Pengfei Zhao; Huilin Li; Chenghui Cai; Xuan Li; Yanying Zhou; Min Huang; Huichang Bi (Chemico-Biological Interactions, 2023)

First record of gray rockcod Lepidonotothen squamifrons larvae in the Amundsen Sea, Antarctic: implication for a new spawning ground and early life characteristics - Huilin Guo; Chi Zhang; Mi Duan; Jianchao Li; Wenchao Zhang; Yongjun Tian (Polar Biology, 2023)

Experimental study on heat transfer characteristics of separated heat pipe with compact structure for spent fuel pool - Yixiang Wu; Jianjie Cheng; Huan Zhu; Huilin Xue; Qingsong Lu; Yannan Li; Wei Li; Hanzhong Tao (Annals of Nuclear Energy, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

A systematic review of electrocoagulation technology applied for microplastics removal in aquatic environment - Fangyuan Liu; Chunpeng Zhang; Huilin Li; Nnanake-Abasi O. Offiong; Yuhang Bi; Rui Zhou; Hejun Ren (Chemical Engineering Journal, 2023)

Cancer cell membrane biomimetic mesoporous silica nanotheranostics for enhanced Ferroptosis-mediated immuogenic cell death on Gastric cancer - Weihong Guo; Zhian Chen; Zhenhao Li; Huilin Huang; Yingxin Ren; Zhenyuan Li; Bingxia Zhao; Guoxin Li; Yanfeng Hu (Chemical Engineering Journal, 2023)

Enhancing ferric ion/sodium percarbonate Fenton-like reaction with tungsten disulfide cocatalyst for metronidazole decomposition over wide pH range - Shiyu Pan; Tongtong Zhao; Huilin Liu; Xiongbo Li; Mengzhen Zhao; Deling Yuan; Tifeng Jiao; Qingrui Zhang; Shoufeng Tang (Chemical Engineering Journal, 2023)

Modeling of velocity and shear stress profiles in the ecological channel with floating vegetation - Jiao Zhang; Wen Wang; Zhanbin Li; Huilin Wang; Yingying Geng (Environmental Science and Pollution Research, 2023)

Novel Metal–Organic Framework Materials In-Focus Detection and Adsorption Cues for Environmental Pollutants - Zhanming Li; Xuejin Mao; Yue Yu; Nali Zhu; Huilin Liu; Nan Xu; Zhongyang Ren; Weihua Peng; Jianjun Zhong; Yufeng Li; Yuxi Gao; Jiating Zhao (Reviews of Environmental Contamination and Toxicology, 2022)

Evaluation of a random displacement model for scalar mixing in ecological channels partially covered with vegetation - Jiao Zhang; Wen Wang; Zhanbin Li; Huilin Wang; Qingjing Wang; Zhangyi Mi (Environmental Science and Pollution Research, 2022)

Study on the deterioration characteristics of greenschist under hydrochemical action and the disaster-causing mechanism in slope - Shaorui Sun; Kai Li; Huilin Le; Jihong Wei; Defei Liu; Jinglei Song; Yongxiang Yu (Bulletin of Engineering Geology and the Environment, 2022)

Synthesis, antifungal activity, and molecular dynamics study of novel geranyl aromatic sulfonamide compounds as potential complex III inhibitors - Xinning Song; Zhiyang Jiang; Jianing Li; Xingxing Lu; Qing Han; Kai Zhu; Huilin Li; Yun Ling; Hongxia Duan (Medicinal Chemistry Research, 2022)

Analyses of the circadian clock genes expression in whole embryos and maternal major tissues of mice - Ximei Cao; Yindi Yan; Xuguang Luo; Xinhua Yang; Huilin Cui; Yanping Yang; Hairong Li (Journal of Molecular Histology, 2022)

Oceanospirillum sediminis sp. nov., Isolated From Coastal Sediment in the Yellow Sea - Huilin Zhao; Yue Tian; Xunke Sun; Qianwen Wu; Si Chen; Jiangfan Shan; Yu Zhong; Xinyu Chen; Xiaoxue Gao; Shengnan Liu; Ruochen Wang; Zongjun Du; et al. (Current Microbiology, 2022)

MicroRNAs sequencing of plasma exosomes derived from patients with atrial fibrillation: miR-124-3p promotes cardiac fibroblast activation and proliferation by regulating AXIN1 - Pengju Zhu; Huilin Li; An Zhang; Zhan Li; Yong Zhang; Manyi Ren; Yujiao Zhang; Yinglong Hou (Journal of Physiology and Biochemistry, 2022)

Submarine Geomorphological Features and Their Origins Analyzed from Multibeam Bathymetry Data in the South China Sea - Xiaolin Ou; Junjiang Zhu; Sanzhong Li; Yonggang Jia; Zhongjia Jia; Shengsheng Zhang; Shaoyu Zhang; Ruixue Chen; Xingquan Chen; Dong Ding; Huilin Xing; Yanhui Suo; et al. (Journal of Marine Science and Engineering, 2021)
We processed the raw multi-beam bathymetry data acquired in the central and northeastern part of the South China Sea by eliminating noise and abnormal water depth values caused by environmental factors, and a high resolution bathymetric map with a 20-m grid interval was constructed. Various scales of seafloor geomorphological features were identified from the data, including an image of Shenhu canyon, which is located in the northern continental margin of the South China Sea; submarine reticular dunes in the north of the Dongsha atoll; submarine parallel dunes in the northeast of the Dongsha atoll; and several seamounts in the southwest sub-basin and in the east sub-basin. In the processing step, various anomalies in the multi-beam bathymetry data were corrected. The optimal swath filtering and surface filtering methods were chosen for different scales of seafloor topography in order to restore the true geomorphological features. For the large-scale features with abrupt elevation changes, such as seamounts (heights of ~111–778 m) and submarine canyons (incision height of ~90–230 m), we applied swath filtering to remove noise from the full water depth range of the data, and then surface filtering to remove small noises in the local areas. For the reticular dunes and parallel dunes (heights of ~2–32 m), we applied only surface filtering to refine the data. Based on the geometries of the geomorphological features with different scales, the marine hydrodynamic conditions, and the regional structure in the local areas, we propose that the Shenhu submarine canyon was formed by turbidity current erosion during the Sag subsidence and the sediment collapse. The submarine reticular dunes in the north of the Dongsha atoll were built by the multi-direction dominant currents caused by the previously recognised internal solitary waves around the Dongsha atoll. The submarine parallel dunes in the northeast of the Dongsha atoll were built by the repeated washing of sediments with the influence of the tidal currents and internal solitary waves. The conical, linear and irregular seamounts identified from the bathymetry data were formed during the spreading of the southwest sub-basin and the east sub-basin. The identified seamounts in the multi-beam bathymetry data are correlated to deep magmatic activities, the Zhongnan transform fault and the NE-trending faults.

Association of gut microbiomes with lung and esophageal cancer: a pilot study - Weitao Shen; Derong Tang; Yali Deng; Huilin Li; Tian Wang; Ping Wan; Ran Liu (World Journal of Microbiology and Biotechnology, 2021)

Catastrophic landslide triggered by persistent rainfall in Sichuan, China: August 21, 2020, Zhonghaicun landslide - Xiaoyu Yi; Wenkai Feng; Huilin Bai; He Shen; Haobin Li (Landslides, 2021)

Effects of Tobacco Stem-Derived Biochar on Soil Properties and Bacterial Community Structure under Continuous Cropping of Bletilla striata - Linyan Zhao; Huilin Guan; Rui Wang; Haoji Wang; Zecheng Li; Wei Li; Ping Xiang; Wumei Xu (Journal of Soil Science and Plant Nutrition, 2021)

Efficient electrokinetic remediation of heavy metals from MSWI fly ash using approaching anode integrated with permeable reactive barrier - Huilin Li; Yi Zheng; Lin Yu; Huirong Lin; Manli Zhang; Binquan Jiao; YanChyuan Shiau; Dongwei Li (Environmental Science and Pollution Research, 2021)

Soil amendment in plastic greenhouse using modified biochar: soil bacterial diversity responses and microbial biomass carbon and nitrogen - Bin Hua; Zhouwen Li; Weikai Gao; Huilin Feng; Nan Chen; Jiayi Li; Xiaoming Ji; Lu Zhang; Zhiyong Wu; Shen Yan; Tianbao Ren; Chensheng Xu; et al. (Biotechnology Letters, 2021)

Vibrio marinisediminis sp. nov., Isolated from Marine Sediment - Huilin Zhao; Jiangfan Shan; Taojie Wang; Yue Tian; Yingjian Shen; Zongjun Du; Boqing Li; Xiaofei Ji (Current Microbiology, 2021)

Halomonas marinisediminis sp. nov., A Moderately Halophilic Bacterium Isolated from the Bohai Gulf - Huilin Zhao; Chaonan Wang; Yue Tian; Yanli Zhang; Yulong Wu; Yan Zhang; Zongjun Du; Boqing Li; Xiaofei Ji (Current Microbiology, 2020)

miR-124-3p promotes BMSC osteogenesis via suppressing the GSK-3β/β-catenin signaling pathway in diabetic osteoporosis rats - Zengying Li; Hengxia Zhao; Shufang Chu; Xuemei Liu; Xin Qu; Jinhua Li; Deliang Liu; Huilin Li (In Vitro Cellular & Developmental Biology - Animal, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Synergism of citric acid and zero-valent iron on Cr(VI) removal from real contaminated soil by electrokinetic remediation - Yi Zheng; Yujie Yan; Lin Yu; Huilin Li; Binquan Jiao; YanChyuan Shiau; Dongwei Li (Environmental Science and Pollution Research, 2020)

Aureibaculum marinum gen. nov., sp. nov., a Novel Bacterium of the Family Flavobacteriaceae Isolated from the Bohai Gulf - Huilin Zhao; Yulong Wu; Cong Zhang; Jiarong Feng; Zheng Xu; Yunfei Ding; Yaxin Gao; Yu Geng; Jie Song; Boqing Li; Xiaofei Ji (Current Microbiology, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

MnO2-loaded microorganism-derived carbon for U(VI) adsorption from aqueous solution - Wei Liao; Huilin Wang; Feize Li; Changsong Zhao; Jun Liu; Jiali Liao; Jijun Yang; Yuanyou Yang; Ning Liu (Environmental Science and Pollution Research, 2019)

Expression, purification, and evaluation of in vivo anti-fibrotic activity for soluble truncated TGF-β receptor II as a cleavable His-SUMO fusion protein - Xiaohua Wang; Yuting Li; Xin Li; Lei Yan; Huilin Guan; Ruijie Han; Yang Han; Jinqiu Gui; Xiaoyan Xu; Yan Dong; Haifeng Liu (World Journal of Microbiology and Biotechnology, 2018)

Native top-down proteomics comes into light - Huilin Li (Science China Life Sciences, 2018)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Herbivore- and MeJA-induced volatile emissions from the redroot pigweed Amaranthus retroflexus Linnaeus: their roles in attracting Microplitis mediator (Haliday) parasitoids - Huilin Yu; Yongjun Zhang; Yunhe Li; Ziyun Lu; Xiangju Li (Arthropod-Plant Interactions, 2018)

Human placenta-derived mesenchymal stem cells loaded on linear ordered collagen scaffold improves functional recovery after completely transected spinal cord injury in canine - Sufang Han; Zhifeng Xiao; Xing Li; Huan Zhao; Bin Wang; Zhixue Qiu; Zhi Li; Xin Mei; Bai Xu; Caixia Fan; Bing Chen; Jin Han; et al. (Science China Life Sciences, 2018)

Biotoxicity of Cry1Ab protein on wolf spider Pardosa pseudoannulata - Juan Wang; Yuande Peng; Huilin Yang; Zhenzhen Yan; Qinjin Li; Yixue Shi; Chunliang Xie; Yunshan Liang; Zhi Wang; Qisheng Song (Ecotoxicology, 2017)

Functionalized hydrothermal carbon derived from waste pomelo peel as solid-phase extractant for the removal of uranyl from aqueous solution - Feize Li; Yu Tang; Huilin Wang; Jijun Yang; Shoujian Li; Jun Liu; Hong Tu; Jiali Liao; Yuanyou Yang; Ning Liu (Environmental Science and Pollution Research, 2017)

Trichophyton rubrum Infection Characterized by Majocchi’s Granuloma and Deeper Dermatophytosis: Case Report and Review of Published Literature - Huilin Su; Li Li; Benlin Cheng; Junhao Zhu; Qiangqiang Zhang; Jinhua Xu; Min Zhu (Mycopathologia, 2017)

Construction of Novel Plasmid Vectors for Gene Knockout in Helicobacter pylori - Xiaofei Ji; Huilin Zhao; Ying Zhang; Xingxing Chen; Jiaojiao Li; Boqing Li (Current Microbiology, 2016)

Effect of cytochrome P450 2C19 polymorphisms on the clinical outcomes of voriconazole: a systematic review and meta-analysis - Xiaofei Li; Caiyuan Yu; Tiansheng Wang; Ken Chen; Suodi Zhai; Huilin Tang (European Journal of Clinical Pharmacology, 2016)

One-year clinical study of NeuroRegen scaffold implantation following scar resection in complete chronic spinal cord injury patients - Zhifeng Xiao; Fengwu Tang; Jiaguang Tang; Huilin Yang; Yannan Zhao; Bing Chen; Sufang Han; Nuo Wang; Xing Li; Shixiang Cheng; Guang Han; Changyu Zhao; et al. (Science China Life Sciences, 2016)

Urinary Tract Infection (UTI) Caused by Fusarium proliferatum in an Agranulocytosis Patient and a Review of Published Reports - Huilin Su; Qiangqiang Zhang; Li Li; Ying Zhao; Junhao Zhu; Min Zhu (Mycopathologia, 2016)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

Decreasing Transmembrane Segment Length Greatly Decreases Perfringolysin O Pore Size - Qingqing Lin; Tong Wang; Huilin Li; Erwin London (The Journal of Membrane Biology, 2015)

Parallel Lattice Boltzmann Computing and Applications in Core Sample Feature Evaluation - Jinfang Gao; Huilin Xing; Victor Rudolph; Qin Li; Sue D. Golding (Transport in Porous Media, 2015)

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies - Baodong Yao; Yujie Yan; Xianwu Ye; Hong Fang; Huilin Xu; Yinan Liu; Sheran Li; Yanping Zhao (Cancer Causes & Control, 2014)

Multiple systemic transplantations of human amniotic mesenchymal stem cells exert therapeutic effects in an ALS mouse model - Haitao Sun; Zongliu Hou; Huaqiang Yang; Mingyao Meng; Peng Li; Qingjian Zou; Lujun Yang; Yuxin Chen; Huihui Chai; Huilin Zhong; Zara Zhuyun Yang; Jing Zhao; et al. (Cell and Tissue Research, 2014)

Glacier volume calculation from ice-thickness data for mountain glaciers—A case study of glacier No. 4 of Sigong River over Mt. Bogda, eastern Tianshan, Central Asia - Puyu Wang; Zhongqin Li; Wenbin Wang; Huilin Li; Feiteng Wang (Journal of Earth Science, 2014)

Production of transgenic mice expressing the goat H-FABP gene by intratesticular injection - Hao Chen; Yanhui Yin; Yani Zhang; Min Sun; Tingfeng Chen; Caiye Zhu; Wei Li; Bichun Li; Huilin Yang (Molecular Biology Reports, 2013)

Effects of Cobalt Nanoparticles on Human T Cells In Vitro - Haitao Jiang; Fan Liu; Huilin Yang; Yang Li (Biological Trace Element Research, 2012)

Ice surface-elevation change and velocity of Qingbingtan glacier No.72 in the Tomor region, Tianshan Mountains, central Asia - Puyu Wang; Zhongqin Li; Huilin Li; Wenbin Wang; Feiteng Wang (Journal of Mountain Science, 2011)

Mechanisms and simulation of accelerated shrinkage of continental glaciers: A case study of Urumqi Glacier No. 1 in eastern Tianshan, Central Asia - Zhongqin Li; Huilin Li; Yaning Chen (Journal of Earth Science, 2011)

On the relationship between local topography and small glacier change under climatic warming on Mt. Bogda, eastern Tian Shan, China - Kaiming Li; Huilin Li; Lin Wang; Wenyu Gao (Journal of Earth Science, 2011)

Application of a degree-day model for determination of mass balance of Urumqi Glacier No. 1, eastern Tianshan, China - Lihua Wu; Huilin Li; Lin Wang (Journal of Earth Science, 2011)

An improved method based on shallow ice approximation to calculate ice thickness along flow-line and volume of mountain glaciers - Huilin Li; Zhongqin Li; Mingjun Zhang; Wenfeng Li (Journal of Earth Science, 2011)

Glacier area variation and climate change in the Chinese Tianshan Mountains since 1960 - Shengjie Wang; Mingjun Zhang; Zhongqin Li; Feiteng Wang; Huilin Li; Yaju Li; Xiaoyan Huang (Journal of Geographical Sciences, 2011)

Chemical characteristics and environmental significance of fresh snow deposition on Urumqi Glacier No. 1 of Tianshan Mountains, China - Zhongqin Li; Huilin Li; Zhiwen Dong; Mingjun Zhang (Chinese Geographical Science, 2010)

Spatial variability and pattern analysis of soil properties in Dehui city, Jilin province - Li Xiaoyan; Zhang Shuwen; Wang Zongming; Zhang Huilin (Journal of Geographical Sciences, 2004)